Prevalence of stress and insomnia among health care workers in India during COVID-19 pandemic: A systematic review and meta-analysis - Ashish W Khobragade; Nitin Agrawal (Wolters Kluwer Medknow Publications, 2023)
Background: Health care workers (HCWs) are prone to stress and insomnia because of pandemic situations. Assessment of the actual burden of this stress and insomnia is essential to form preventive strategies. The study's objective was to find out the pooled prevalence of stress and insomnia among HCWs in India during the coronavirus disease (COVID-19) pandemic. Material and Methods: We conducted a systematic review and meta-analysis to determine the prevalence of stress and insomnia among HCWs during the COVID-19 pandemic in India. Cross-sectional studies conducted in India regarding stress and insomnia among HCWs were searched from PubMed, Scopus, Embase, and Google Scholar. These studies were published after the declaration of the COVID-19 pandemic till August 31, 2021. Articles were searched independently by both authors. Data were extracted in an Excel sheet and analyzed using the 'Meta' package of the 'R' software version 4.1.0. Result: A total of 23 and 16 studies were included in the final pooled analysis of stress and insomnia, respectively, following preferred reporting items for systematic review and meta-analysis guidelines. A random-effects model was used to determine the pooled prevalence of stress and insomnia. This study is registered in Prospero. The registration number is CRD42021253917. The total numbers of HCWs from India included were 8125 and 4974, respectively, for finding out the pooled prevalence of stress and insomnia. The pooled prevalence of stress and insomnia among HCWs is 43% [95% confidence interval (CI) 30-56%] and 35% (95% CI 28-44%), respectively. Two out of five and one in three Indian HCWs have stress and insomnia, respectively, during the COVID-19 pandemic. Conclusion: Human resource development should be prioritized to decrease the workload among HCWs. The findings from this study will be useful in preparing policy guidelines on mental health screening of HCWs during the pandemic.